Pine mistletoe (Viscum album ssp. austriacum (Wiesb.) Vollm.) in pine forests of Ukraine: current state of the problem - Орлов , О. О.; Жуковський , О. В.; Бородавка , В. О.; Бородавка , О. Б.; Шевчук , В. В.; Матейчик , В. І.; Арват , Л. С. (Forestry and Forest Melioration, 2023)
Introduction In conditions of global climate change and increasing aridity, the weakening of pine forests has been observed. In the last 10–15 years a new threat for pine forests of Ukraine has appeared, namely a lesion by a semi-parasitic species pine mistletoe (Viscum album ssp. austriacum (Wiesb.) Vollm.). The purpose of the study was to analyze the main biological and ecological traits of pine mistletoe, to identify the areas of its vast distribution in the pine forests of Ukraine, and to evaluate the main indexes, productivity, and forest health of the pine stands affected by mistletoe. Materials and Methods We analysed herbarium collections, literary data, floristic databases, and databases of forest health surveys of pine stands affected by pine mistletoe. We also used methods of forest science and comparative ecology. Results Nowadays pine mistletoe is typically classified as a subspecies of white mistletoe (Viscum album ssp. austriacum (Wiesb.) Vollm.), as confirmed via molecular-genetic study. It primarily grows on crown branches of coniferous trees, such as various Pinus L. species. It can also be found on Picea A. Dietr. and Larix Mill. branches, although this is less common. In Ukraine, the species has only been observed growing on Scots pine. Pine mistletoe is an ornitochore, and its seeds are primarily dispersed by birds, including Turdus viscivorus Linnaeus, 1758, Bombycilla garrulus Linnaeus, 1758, and Sylvia atricapilla Linnaeus, 1758. Research shows that pine mistletoe primarily colonizes dominant trees with large crowns and roots in pine stands. It is important to note that this species demonstrates specificity in host selection. The first reports of pine mistletoe in Ukraine were recorded in the 1940s to 1950s in Polissia. Currently, pine stands infected by pine mistletoe have been found in various regions of the country: the zone of mixed forests, Polissia region, physical-geographical areas of Volyn Polissia, Zhytomyr Polissia, Kyiv Polissia, and Chernihiv Polissia. Additionally, occurrences have been noted in the Forest-Steppe zone, Podilsko-Prydniprovsky region, Kyiv highland area, and Central-Prydniprovsky highland area. According to our estimates, the pine mistletoe has infected a total area of roughly 13,500 hectares of pine forests. This comprises approximately 2,100 hectares in Polissia and 11,400 hectares in the Forest-Steppe zone. The majority of the infested stands consist of overmature (54%), pure pine stands (72%), with high growth classes (57%) and average density (67%). Pine mistletoe is distributed in the nature reserve fund of Ukraine, in particular in nature reserves Rivnensky, Cheremsky, Polisky and Drevliansky; national natural parks Shatsky, Holosiyvsky, Prypiat-Stokhid; the botanical reserve of the state significance Lisnyky, the botanical reserves of the local significance Mykhailivsky and Dakhnivsky, the zoological reserve of the local significance Imshan, the landscape reserve of the local significance Obukhivsky. Currently the pine mistletoe control in Ukraine is hampered due to the fact that in Volyn Region and Zhytomyr Region it is included into the lists of rare and protected plant species. Conclusions Now in Ukraine, there is a lack of data on the distribution and area of pine stands infected by pine mistletoe as well as the dynamics of species spreading in the last 5–10 years. Besides, there is no data concerning the influence of the species on the health state and productivity of pine stands. Thus, the infection of pine forests by pine mistletoe should be considered on the national level. Colonization of pine by mistletoe decreases the vitality of infected trees, which leads to the defoliation and the death of shoots, and a decrease in annual growth. During a drought, it can bring about the death of the whole host tree. In Ukraine, it is necessary to develop a comprehensive study of pine mistletoe in pine forests which, in turn, should result in appropriate forest management measures for the pine stands affected by Viscum album ssp. austriacum. 5 Figs., 58 Refs.